2007
DOI: 10.7202/016170ar
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation des résidus industriels de pêches pour la transformation de chitosane par technique hydrothermo-chimique

Abstract: Tous droits réservés © Revue des sciences de l 'eau, 2007 Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'Université de Montréal, l'Université Laval et l'Université du Québec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…These variations may be affected by the different nature of raw material and the parameters of deacetylation process (time and temperature). Truong et al (2007) [7] and Kumar (2000) [17] reported that the DD% necessary to obtain a chitosan product is 65% or higher. Ash content indicates the effectiveness of the demineralization step, No et al (1995) [18] reported that chitosan of a good quality must have less than 1% of ash content, which is in agreement with the results obtained in this study (0.94%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations may be affected by the different nature of raw material and the parameters of deacetylation process (time and temperature). Truong et al (2007) [7] and Kumar (2000) [17] reported that the DD% necessary to obtain a chitosan product is 65% or higher. Ash content indicates the effectiveness of the demineralization step, No et al (1995) [18] reported that chitosan of a good quality must have less than 1% of ash content, which is in agreement with the results obtained in this study (0.94%).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan was obtained after the two following steps: acid demineralization followed by simultaneous deproteinization and deacetylation by hydrothermal-chemical method in an alkali environment, with a solid-liquid ratio of 1:10 w/v (weight of dry shell / volume of diluted solution), according to the method described by Truong et al (2007) [7] with some modifications.…”
Section: Chitosan Extractionmentioning
confidence: 99%
“…High temperatures are used for very short periods (20-30 min), as reported by Kaya et al 100 and Monter-Miranda et al 119 In contrast, longer treatment periods (12-24 h) are applied for incubations done at room temperature. 106,114,123 High temperatures promote the penetration of the solvent into the chitin matrix 145 ; however, they can cause polymer degradation. 25 The efficiency of demineralization (DME) can be evaluated by assessing the mineral content of insect samples before (MC BT ) and after treatment (MC AT ) according to the following equation:…”
Section: Chitin Purificationmentioning
confidence: 99%
“…The deacetylation reaction is rarely complete, to avoid a sharp reduction in the molecular weight of the polymer. The use of high temperatures generally improves the reaction rates and yields [25]. Ultrasound and microwave technologies were also proposed to enhance the extraction and deacetylation steps [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%